2019
DOI: 10.1371/journal.pone.0214994
|View full text |Cite
|
Sign up to set email alerts
|

Fat-to-muscle ratio is a useful index for cardiometabolic risks: A population-based observational study

Abstract: Metabolic disorders are prevalent worldwide and have recently become public health problems recently. Previous studies have proposed different body composition indices for predicting future cardiovascular risks. We hypothesized an association among fat-to-muscle ratio (FMR), metabolic syndrome (MetS), hypertension (HTN), prediabetes, type 2 diabetes mellitus (DM), and cardiovascular risk in an adult population. A total of 66829 eligible subjects composed of 34182 males and 32647 females aged 20 years or older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 46 publications
(49 reference statements)
3
32
0
2
Order By: Relevance
“…Meanwhile, it has been reported that the FM/FFM ratio was positively associated with insulin resistance in the general population and liver fat accumulation, which was an important pathological feature of NAFLD, in patients with T2D directly [ 18 , 35 ]. Besides, studies also suggested that the FM/FFM ratio was capable to be regarded as a novel predictor of metabolic syndrome and glucose metabolic disorder, which both were associated closely with NAFLD [ 18 20 , 36 ]. Combined these studies with the findings of our study, the FM/FFM ratio could be a useful predictor of the risk of developing NAFLD among different obesity status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, it has been reported that the FM/FFM ratio was positively associated with insulin resistance in the general population and liver fat accumulation, which was an important pathological feature of NAFLD, in patients with T2D directly [ 18 , 35 ]. Besides, studies also suggested that the FM/FFM ratio was capable to be regarded as a novel predictor of metabolic syndrome and glucose metabolic disorder, which both were associated closely with NAFLD [ 18 20 , 36 ]. Combined these studies with the findings of our study, the FM/FFM ratio could be a useful predictor of the risk of developing NAFLD among different obesity status.…”
Section: Discussionmentioning
confidence: 99%
“…There were several studies that investigated the associations of FM/FFM with health outcomes and found that the ratio was associated with insulin resistance, liver fat accumulation, glucose metabolic disorders, and metabolic syndrome [ 18 20 ]. However, the association of the FM/FFM ratio with the risk of incident NAFLD and fibrosis remained unclear, especially whether it could predict the NAFLD risk in non-obese individuals has not been estimated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested the potential usefulness in managing metabolic diseases of an index that combines muscle mass and fat mass [ 17 , 18 ]. Previously, we reported that BMFR has a strong linear correlation with M/I [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The greatest percent of prevalence of the hypertension (H) is fixed in such sports as weightlifting, American soccer and baseball where athletes reach the body weight of ≥136 kg (Weiner et al, 2013). Also, the burden of H from 55.4 % to 83 % is noted in a subgroup of athletes of power sports of heavy weight category (Chobanian et al, 2003;Guo et al, 2013). Physical exercise is a cornerstone in non-pharmacological hypertension therapy.…”
Section: Introductionmentioning
confidence: 99%